Influence of cardiopulmonary bypass on the erythrocyte membranes and the method of its protection - Cherniy , V.І.; Sobanska, L.O.; Topolov, P.O.; Сherniy, T.V. (Medicni Perspektivi, 2021)
The damage to erythrocytes during cardiopulmonary bypass (CPB) remains a recent problem. The aim of this research was to study the effect of fructose-1,6-diphosphate on the state of the erythrocyte membrane during CPB and the level of phosphorus in blood as a marker of the energy potential in the cell. Patients were divided into two groups. The control group 1 (Gr 1) consisted of 75 individuals. The group 2 (Gr 2) included patients to whom fructose-1,6-diphosphate (FDP) was administrated according to the developed scheme as follows 10 g of the drug was diluted in 50 ml of a solvent, 5 g of the drug was injected intravenously with the use of perfusor immediately before initiation of CPB at a rate of 10 ml/min and 5 g at the 30th minute of CPB (before the stage of warming) the same way. When comparing two groups the best results in hemolysis (p<0.01), mechanical (p<0.01). osmotic resistance of erythrocytes (p<0.01), the time of acid hemolysis (p<0.01) and the permeability of the erythrocyte membrane in postperfusion period were in Gr 2. Вefore cardiac surgery hypophosphatemia was detected in 18% out of 150 and in 32% out of 150 patients – a lower limit of normal phosphorus content in the blood. After CPB in Gr 1 phosphorus content in blood was 0.85±0.32 mmol/l and hypophosphatemia was in 53% out of 75 patients. This indicates a pronounced energy deficit in this group. In Gr 2 phosphorus level was 1.7±0.31 mmol/l and there was no hypophosphatemia. As a result, FDP as an endogenous high-energy intermediate metabolite of the glycolytic pathway leads to resistance to hemolysis, protects the erythrocyte membrane from damage and increases the energy potential of the cell during CPB.